Better Practices in the Development and Validation of Recidivism Risk Assessments: The Minnesota Sex Offender Screening Tool–4: - Duwe, Grant (Criminal justice policy review, 2019)
This study examines the development and validation of the Minnesota Sex Offender Screening Tool-4 (MnSOST-4) on a dataset consisting of 5,745 sex offenders released from Minnesota prisons between 2003 and 2012. Bootstrap resampling was used to select predictors, and k-fold and split-sample methods were used to internally validate the MnSOST-4. Using sex offense reconviction within 4 years of release from prison as the failure criterion, the data showed that 130 (2.3%) offenders in the overall sample were recidivists. Multiple classification methods and performance metrics were used to develop the MnSOST-4 and evaluate its predictive performance on the test set. The results from the regularized logistic regression algorithm showed that the MnSOST-4 performed well in predicting sexual recidivism in the test set, achieving an area under the curve (AUC) of 0.835. Additional analyses on the test set revealed that the MnSOST-4 outperformed the Minnesota Sex Offender Screening Tool-3 (MnSOST-3), Minnesota Sex Offender Screening Tool-Revised (MnSOST-R), and Static-99 in predicting sexual reoffending.